2014
DOI: 10.1039/c3cp53855a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of La-doping on phase transformation and photocatalytic properties of ZnTiO3nanoparticles synthesized via modified sol–gel method

Abstract: Non-doped and La-doped ZnTiO3 nanoparticles were successfully synthesized via a modified sol-gel method. The synthesized nanoparticles were structurally characterized by PXRD, UV-vis DRS, FT-IR, SEM-EDS, TEM, Raman and photoluminescence spectroscopy. The results show that doping of La into the framework of ZnTiO3 has a strong influence on the physico-chemical properties of the synthesized nanoparticles. XRD results clearly show that the non-doped ZnTiO3 exhibits a hexagonal phase at 800 °C, whereas the La-dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…In particular, the photoluminescence (PL) properties are an important quantum optical phenomenon and are one of the most powerful methods for studying the order-disorder effects in semiconductors [8,9]. The doping process in semiconductors often causes significant alterations in the structural and electronic properties of these materials, and is the most promising strategy to further enhance their properties and applications in materials science [5,6,[15][16][17]. However, few studies have been reported on near-infrared (NIR) emissions for such particles [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the photoluminescence (PL) properties are an important quantum optical phenomenon and are one of the most powerful methods for studying the order-disorder effects in semiconductors [8,9]. The doping process in semiconductors often causes significant alterations in the structural and electronic properties of these materials, and is the most promising strategy to further enhance their properties and applications in materials science [5,6,[15][16][17]. However, few studies have been reported on near-infrared (NIR) emissions for such particles [14].…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite structures have the general formula ABO 3 , where the divalent metal (A) is a network modifier and tetravalent metal sites (B) are network formers for these structures [2]. The Perovskite material ABO 3 structure can adopt five phases, cubic, tetragonal, orthorhombic, trigonal, and monoclinic polymorphs depending on the tilting and rotation of the [BO 6 ] polyhedral clusters in the lattice [3]. In this context, considerable effort has been devoted to the production of perovskite oxide materials with a large variety of morphologies and sizes, due to their high potential for use in lightemitting diodes, photocatalysts, sensors, microwave dielectrics, and photovoltaic applications [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, ZnO nanoparticles also exhibiting antimicrobial activities against Escherichiacoli and Staphylococcus aureus [7][8][9][10][11]. Several researchers reported doping of ZnO with metals such as Mn, Co, Cr, Cu, In and Laby various methods such as hydrothermal, sol-gel and coprecipitation method but only few reports are available ZnO doped with Al and Y [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%